A Neurophenomenology of Awe and Wonder - Gallagher, Shaun. author. aut Link
IX, 195 p.
Keywords: This book presents a study of the various feelings of awe and wonder experienced by astronauts during space flight. It summarizes the results of two experimental, interdisciplinary studies that employ methods from neuroscience, psychology, phenomenology and simulation technology, and it argues for a non-reductionist approach to cognitive science.